2000
DOI: 10.1177/10778010022181903
|View full text |Cite
|
Sign up to set email alerts
|

Women Filing Assault Charges on an Intimate Partner

Abstract: To describe the criminal justice outcomes and violence experienced after women seek to file assault charges against an intimate partner, 90 women were interviewed and followed for six months. Threats of violence, physical assault, stalking, and danger were measured by interview questionnaires at the time of filing charges and at 3 and 6 months later. Among the 90 women, 48% had insufficient evidence for charges; of the 52% making charges, 11% dropped charges, 37% of the perpetrators were arrested, and 4% remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Secondary data analysis also means that only cases that result in arrest are included in the analysis. Not all victims report stalking, as shown in Bjerregaard (2000) where only 10% of victims contacted police, and reporting a case of intimate violence to law enforcement does not always lead to arrest, as evidenced in the McFarlane, Willson, Lemmey, and Malecha (2000) study of reports to police by 90 abused women, 48% of which were found insufficient to result in charging of the offender. Also, the data sources for this study do not reveal whether stalking charges were amended due to inappropriate application of the charges at the time of the arrest or if they were amended due to prosecutors' lack of confidence about getting a conviction.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary data analysis also means that only cases that result in arrest are included in the analysis. Not all victims report stalking, as shown in Bjerregaard (2000) where only 10% of victims contacted police, and reporting a case of intimate violence to law enforcement does not always lead to arrest, as evidenced in the McFarlane, Willson, Lemmey, and Malecha (2000) study of reports to police by 90 abused women, 48% of which were found insufficient to result in charging of the offender. Also, the data sources for this study do not reveal whether stalking charges were amended due to inappropriate application of the charges at the time of the arrest or if they were amended due to prosecutors' lack of confidence about getting a conviction.…”
Section: Discussionmentioning
confidence: 99%
“…Independent estimates of the percentage of women who report domestic assaults to police range from 7% to 14% (Kantor & Straus, 1990), compared with official U.S. Department of Justice figures of approximately half of partner violence incidents against White women and two thirds of incidents against Black women being reported by the victims (Greenfield et al, 1998). Among the fraction of incidents known to police, almost half (48%) of the women were judged to have insufficient evidence for filing or acceptance of charges (McFarlane, Willson, Lemmey, & Malecha, 2000). There were no differences in the levels of violence contained within charges that were accepted and those rejected.…”
Section: Partner Violencementioning
confidence: 92%
“…This conflict and the perceived disruptions in the social support offered after the RCO is administered may lead to reduced amounts of PSS experienced by both IACV and ITV. Additionally, IACV may also receive generally negative responses from members of their social support network due to the stigma connected to their exposed criminal behavior [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Attachment Theory (Bowlby)mentioning
confidence: 99%